2012
DOI: 10.1371/journal.pone.0051719
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Scale Genomic DNA Copy Number Aberrations as Another Means of Mutagenesis in Breast Cancer

Abstract: IntroductionIn breast cancer, the basal-like subtype has high levels of genomic instability relative to other breast cancer subtypes with many basal-like-specific regions of aberration. There is evidence that this genomic instability extends to smaller scale genomic aberrations, as shown by a previously described micro-deletion event in the PTEN gene in the Basal-like SUM149 breast cancer cell line.MethodsWe sought to identify if small regions of genomic DNA copy number changes exist by using a high density, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…FSIP2 amplifications were all 8–9 kb in length spanning a sub-region of the gene coding sequence, encompassing exons 16–17. Recent functional evidence has demonstrated that part-gene amplifications do affect gene expression levels, with an effect size comparable to that of full-gene amplification 37 . Our finding of recurrent FSIP2 amplification is corroborated by recent high resolution SNP array data on an independent series of seminomas 38 , which documented FSIP2 amplification in 22% of tumours.…”
Section: Resultsmentioning
confidence: 99%
“…FSIP2 amplifications were all 8–9 kb in length spanning a sub-region of the gene coding sequence, encompassing exons 16–17. Recent functional evidence has demonstrated that part-gene amplifications do affect gene expression levels, with an effect size comparable to that of full-gene amplification 37 . Our finding of recurrent FSIP2 amplification is corroborated by recent high resolution SNP array data on an independent series of seminomas 38 , which documented FSIP2 amplification in 22% of tumours.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we find that both EGFR and PTEN are localized to short-lived CCPs. We examined the role of PTEN more closely by reconstituting PTEN in triple-negative inflammatory breast cancer SUM149 cells, which do not express functional PTEN due to a genetic micro-amplification within the PTEN gene (Saal et al, 2008;Chao et al, 2012), and by deleting PTEN in MCF10A and MDA231 cells. By analyzing CCP dynamics, we demonstrate a role for PTEN in regulating the proportion of short-lived CCPs and initiation density.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, we find that both EGFR and PTEN are localized to short-lived CCPs. We examined the role of PTEN more closely by reconstituting PTEN in triple negative inflammatory breast cancer SUM149 cells, which do not express functional PTEN due to a genetic micro-amplification within the PTEN gene 35,36 , and by deleting PTEN in MCF10A and MDA231 cells. By analyzing CCP dynamics, we demonstrate a role for PTEN in regulating the proportion of short-lived CCPs and initiation density.…”
Section: Introductionmentioning
confidence: 99%